PENGARUH KONDISI KEUANGAN PEMERINTAH KABUPATEN DAN KOTA TERHADAP KASUS COVID 19: STUDI EMPIRIS PADA PEMERINTAH DAERAH DI KALIMANTAN BARAT - indriani, ika; Hendri Prasetyo; Agus Widodo (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2020)
The analysis of financial conditions aims to provide an overview of the ability of the regions to carry out their duties and functions in order to realize the country's goals in the midst of the COVID-19 pandemic. The COVID-19 pandemic is a new challenge for local governments in realizing the country's goals. The COVID-19 pandemic will have a direct impact on regional financial management and the implementation of regional programs. this study uses a descriptive quantitative approach with secondary data in the form of a 2010-2019 budget realization report. The results showed that the financial condition of the district and city governments in West Kalimantan was in fairly good condition during 2010 to 2019. The solvency of the government budget was in good condition with a ratio value of 1.2015; 1,2013; 2.1793; and 1.0128. The government's financial independence is in low condition due to being vulnerable to other funding sources, as indicated by the ratio values ​​of 0.0597 and 0.0600. The solvency of services is in good condition with the total budget and capital expenditures that can finance the provision of public services of Rp3.072.878 and Rp705.509, respectively. Simultaneously, financial conditions have a significant effect on COVID-19 cases in local government in West Kalimantan. partially the ratio of budget solvency, financial independence, and solvency of local government services have an effect on the covid 19 case.